Effect of Power Factor on Combination of Fluorescent with LED Tubes - Srisuwan, Khomkrit; Skulphong, Rak (Journal of Advanced Development in Engineering and Science, 2023)
This paper examines the effect of power factor in the case of LED tubes combined with fluorescent tubes. The properties of LED tubes are capacitive load and fluorescent tubes is inductive load. Therefore, when both lamps are used together, the reactive power will compensate each other. And increase the power factor of the lighting system. The experiments showed that a fluorescent tubes combined with 2 LED tubes to an increase the power factor of 0.69, which compared to fluorescent and LED tubes are 0.51 and 0.52 respectively.